Design, synthesis, and evaluation of inhibitors of InhA to prevent cell wall biosynthesis in Mycobacterium bovis - Stevenson, Matthew (2020)
Tuberculosis is a disease primarily affecting the lungs caused by Mycobacterium bovis (Mycobacterium tuberculosis in humans) which is transmitted via airborne droplets through mucosal fluids. It is classified as both a major health threat and cattle farming threat as well as a leading cause of death worldwide ranked alongside HIV and in 2016, 1.6 million people died as a result of the disease. It is a particular problem in the farming industry where culling of livestock is generally utilised rather than expensive and lengthy treatment. Most recent statistics from the UK indicated 4,395 new contaminated herds with over 44,000 animals slaughtered due to the disease. The nature of treatment (long-term combination therapy) as well as unwillingness to vaccinate cattle breeds resistance, the subject of which is a growing issue with both multidrug (MDR-TB) and extensively drug resistant (XDR-TB) tuberculosis strains becoming increasingly prevalent worldwide. Isoniazid (INH) is a prodrug activated by KatG, the active form then inhibits InhA. INH is one of the most potent antitubercular drugs which acts to prevent the production and replenishment of mycolic acids, which form the outer coat of the Mycobacterium, by inhibiting the FASII section of the fatty acid biosynthetic pathway. Mutation in KatG renders the prodrug inert but by targeting InhA directly we can still inhibit production of mycolic acids, and as InhA has an identical structure in bovis as in tuberculosis there is the potential for treating both humans and cattle. Work has been carried out on the synthesis of a new class of potential inhibitors based on L-ascorbic acid, which as a readily available starting material that shows little to no toxicity in the body provides an interesting route for drug development. These compounds are considered a second generation of inhibitors compared to the work of Manjunatha et al who screened the Novartis compound library and found 4-hydroxy-2-pyridones had potent antitubercular activity against InhA.